Strategy for Increasing Police Accountability and Professionalism through Evaluation of Preventive and Repressive Efforts against Authority Abuse (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2025)
Increasing police accountability and professionalism is critical in addressing abuses of authority within law enforcement institutions. These issues have become a major concern, especially when abuses undermine public trust and the integrity of law enforcement agencies. To overcome these challenges, a comprehensive approach that includes both preventive and repressive measures is necessary. Preventive efforts such as ethics education, professional training, and mental development programs are essential in cultivating a culture of integrity and professionalism within the police force. These initiatives help officers to better understand their responsibilities, adhere to ethical standards, and manage the psychological demands of their roles. On the other hand, repressive efforts, including law enforcement and the imposition of strict sanctions for violations, act as deterrents to unethical behavior. The effective enforcement of laws and policies is critical in holding officers accountable and ensuring that those who abuse their power are appropriately disciplined. Analyzing the implementation of ethics in police duties and the factors that either support or hinder both internal and external supervision is also necessary. By identifying weaknesses in the existing system, law enforcement agencies can better target areas that need reform. Furthermore, strengthening transparency within the police force and reforming the supervision system are crucial steps toward building public trust. Public participation in external supervision mechanisms is also a key factor. When citizens are actively involved in oversight, it fosters a sense of accountability and encourages police officers to act with more responsibility. In conclusion, by adopting an evaluation-based approach and pursuing reforms aimed at enhancing accountability and professionalism, police institutions can improve their effectiveness. These reforms will promote fairer, more transparent, and responsible law enforcement, ultimately leading to greater public confidence in the police and their ability to perform their duties justly.